Immunization safety review : hepatitis B vaccine and demyelinating neurological disorders - Stratton, Kathleen R.; Almario, Donna A.; McCormick, Marie C. (National Academies Press, 2002)
Immunization to protect infants and children from vaccine-preventable diseases is one of the greatest achievements of public health. Immunization is not without risks, however. It is well established, for example, that the oral polio vaccine can on rare occasion cause paralytic polio.The Immunization Safety Review Committee was established by the Institute of Medicine (IOM) to evaluate the available evidence on a series of immunization safety concerns. The committee is charged with examining three immunization safety hypotheses each year during the three-year study period (2001- 2003). While all of the committee members share the view that immunization is generally beneficial, none of them has a vested interest in the specific immunization safety issues that come before the group. In this report, which is the fourth in the series, the committee examines the hypothesis that the hepatitis B vaccine increases the risk for demyelinating disorders of the central or peripheral nervous systems, including multiple sclerosis (MS) and Guillain-Barr syndrome (GBS).